1997
DOI: 10.1182/blood.v90.11.4522
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Dissemination of Lewis Lung Carcinoma in Plasminogen-Deficient Mice

Abstract: Plasminogen activation has been proposed to play a critical role in cancer invasion and metastasis. The effects of complete ablation of plasminogen activation in cancer was studied by inoculation of a metastatic Lewis lung carcinoma expressing high levels of plasminogen activator into plasminogen-deficient (Plg−/−) mice and matched control mice. Primary tumors developed in all mice with no difference in the rate of appearance between Plg−/− and control mice. However, the primary tumors in Plg−/− mice were smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(11 citation statements)
references
References 46 publications
0
10
1
Order By: Relevance
“…Several studies have shown that plasmin activation does not play a major role in the subcutaneous growth of primary tumors. It has been shown that sub-cutaneous inoculation of plasminogen negative tumour cells (LLC) in plasminogen-null mice produced tumors only 10-35% smaller compared to control mice [ 38 ], while we observed a 70-85% decrease in tumor volume in the A549 and HT1080 ANXA2 depleted tumors compared to control tumors. Another study showed that both WT and plasminogen-null mice carrying the Polyoma middle T antigen under the control of the mouse mammary tumor virus long terminal repeat uniformly developed multiple bilateral mammary tumors that were indistinguishable [ 39 ].…”
Section: Discussioncontrasting
confidence: 54%
“…Several studies have shown that plasmin activation does not play a major role in the subcutaneous growth of primary tumors. It has been shown that sub-cutaneous inoculation of plasminogen negative tumour cells (LLC) in plasminogen-null mice produced tumors only 10-35% smaller compared to control mice [ 38 ], while we observed a 70-85% decrease in tumor volume in the A549 and HT1080 ANXA2 depleted tumors compared to control tumors. Another study showed that both WT and plasminogen-null mice carrying the Polyoma middle T antigen under the control of the mouse mammary tumor virus long terminal repeat uniformly developed multiple bilateral mammary tumors that were indistinguishable [ 39 ].…”
Section: Discussioncontrasting
confidence: 54%
“…Fibrin remodeling is involved in numerous steps of metastasis and has been shown to perform a crucial role in the formation of new vessels ( 42 ) Cross-linked fibrin in the ECM serves as a stable framework for endothelial cell migration during angiogenesis and for tumor cell migration during invasion ( 43 ). Knockout mouse models have also revealed the importance of fibrin remodeling in tumor growth and metastasis ( 44 ). In addition, multivariate modeling showed an association between the presence of elevated D-dimer levels and the presence of visceral metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The dependence of tumor growth on host plasminogen was demonstrated also in the foot pad model with Lewis lung carcinoma and T241 fibrosarcoma [ 60 ]. Surprisingly, no quantitative differences were observed in lung metastasis between plasminogen knock-out and control mice if the Lewis lung carcinoma cells were implanted subcutaneously [ 61 ], pointing to complexity of plasminogen functions, manifestation of which in cancer can depend on the site of tumor development. Plasminogen-deficient mice also manifest a significantly decreased angiogenic response to vascular endothelial growth factor (VEGF) or basic fibroblast growth factor (bFGF or FGF-2), which clearly indicates the importance of the plasmin system in angiogenesis in vivo [ 62 ].…”
Section: Specific Functions Of In Vivo Generatementioning
confidence: 99%